INVESTIGATING THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE (AI) IN COVID-19 PANDEMIC- A REVIEW - Dr. Sadun Mohammed Alageel Albaiji 1*, Fahad Mohammad Albaiji 2, Ahmed Hawash Alshammari3, Meshal Hammad Alshammary4, Fadi Fahad Alshammari 5, Hamad Ghafel Aldhafeeri 6, Abdulrahman Murhij Aldhafeeri7 (Chelonian Research Foundation, 2022)
In recent years, Internet of Things (IoT), Big Data, Artificial Intelligence (AI), and Machine Learning are some of the new technologies that healthcare delivery needs to embrace in order to combat and anticipate emerging diseases. Reviewing AI's function as a cutting-edge tool for analysis, avoidance and the fight contrary to COVID-19 (the coronavirus) and further pandemics is our goal. The COVID-19 pandemic has placed the whole globe in an unparalleled and challenging condition, causing a complete cessation of living activities and resulting in the loss of thousands of human beings. COVID-19 is currently present in 212 nations and territories, resulting in a total of May 22, 2020, there were 5,212,172 infected cases and 334,915 deaths. This poses a significant threat to the public health system. Approaches: A comprehensive literature review was conducted utilizing the Google Scholar, Scopus, and PubMed databases, focusing on the keywords The Coronavirus (COVID-19) with Artificial Intelligence (AI). Gathered the most recent data on AI concerning COVID-19 and subsequently investigated it to find possible uses for this condition. KEYWORDS- Big data, machine learning, IOT, artificial intelligence, bioinformation etc.